(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
The Proton Exchange Membrane (PEM) fuel cell performance not only depends on temperature but also depends on the operating pressure, which will increase the performance of the PEM fuel cell. The PEM fuel cell with serpentine flow field was modeled using Solidworks software and analyzed using ANSYS software. By analysis of three different pressures on the PEM fuel cell, and came to know that the optimum pressure gives the best performance. The peak power density occurs in the constant temperature of 323 K with the pressure of 2 bar.